PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN JAHE MERAH (ZINGIBER OFFICINALE ROSCOE) DALAM MENURUNKAN TEKANAN DARAH PENDERITA HIPERTENSI DI DESA TARATARA SATU - Langingi, Ake (Journal of Excellence Humanities and Religiosity, 2024)
High blood pressure, also known as hypertension, is a non-communicable disease (NCD), which is a condition where blood pressure increases above the normal threshold of 120/80 mmHg; this includes an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements taken over five minutes in a resting or calm state. Red ginger also functions to lower blood pressure because the compounds contained in ginger have a mechanism that can inhibit the activity of angiotensin-converting enzyme (ACE) so that it can reduce high blood pressure. The aim of this activity is to empower the community in the use of red ginger (Zingiber officinale Roscoe) in reducing blood pressure in hypertension sufferers in Taratara Satu Village. The method used in this activity is the lecture method and providing education about the benefits of red ginger. Based on the results of PKM activities in Taratara Satu Village, Tomohon City, the results showed that there was an increase in public knowledge about the use of red ginger in lowering blood pressure in the community in Taratara Satu Village. It can be concluded that there has been an increase in public knowledge about the use of red ginger in lowering blood pressure in the community in Taratara Satu Village. As a suggestion for the public, to make more use of red ginger extract as part of complementary therapy to lower blood pressure.